CASE STUDY OF DESIGNING AND MAKING A COMMUNITY PARK MODEL PROJECT - Mathivathany, S.; Ushanthini, R. (University of Jaffna, 2019)
A community park is one of the most publicized built examples of sustainable community design and landscape. Parks provide space for neighborhood residents to interact with each other and meet new people. They are also great spaces for events and for people to engage in recreational activities which allow people to develop a sense of community (Casandra, 2018). The purpose of this case study is to make this knowledge available to practitioners and researchers as well as to provide a design and make a community park project by using available potentials resources. Trincomalee Town is recognized as a region that has a lot of potential sites and home to famous sites for people to engage in recreational activities. Beach along with the Trincomalee town, nearly 5.6 Acer land is available which is famous Back Bay and for leisure activities within Trincomalee District. This land is polluted and underutilized in the city limit, which is the only available land for open space development. Therefore, this research was conducted in the Trincomalee at Back Bay Water Front with the objectives to assess the present situation of the area, to analysis the site suitability with identified factors, to propose strategic project and provide a detail design for a new community park project with comparison of the world sites based on the best practices to change proposed site in a better way.
Keywords: Leisure activities; potentials resources; recreational activities; sustainable community design,; strategic project